Collagen VI Is a Gi-Biased Ligand of the Adhesion GPCR GPR126/ADGRG6 - Caroline Wilde; Paulomi Mehta Chaudhry; Rong Luo; Kay-Uwe Simon; Xianhua Piao; Ines Liebscher (Cells, 2023)
GPR126/ADGRG6, a member of the adhesion G-protein-coupled receptor family, balances cell differentiation and proliferation through fine-tuning of intracellular cAMP levels, which is achieved through coupling to Gs and Gi proteins. While GPR126-mediated cAMP increase has been proven to be essential for differentiation of Schwann cells, adipocytes and osteoblasts, Gi-signaling of the receptor was found to propagate breast cancer cell proliferation. Extracellular ligands or mechanical forces can modulate GPR126 activity but require an intact encrypted agonist sequence, coined the Stachel. Even though coupling to Gi can be seen for constitutively active truncated receptor versions of GPR126 as well as with a peptide agonist derived from the Stachel sequence, all known N-terminal modulators have so far only been shown to modulate Gs coupling. Here, we identified collagen VI as the first extracellular matrix ligand of GPR126 that induces Gi signaling at the receptor, which shows that N-terminal binding partners can mediate selective G protein signaling cascades that are masked by fully active truncated receptor variants.